Inclusiveness in governance : Caribbean considerations and experiences. - Ragoonath, Bishnu ed. (Urban Management Programme, 2011)
Offers an understanding of good governance, particularly as it relates to attempts at institutionalising such practices within the Caribbean.
Keywords: GOVERNANCE; DEMOCRACY; POVERTY; LOCAL GOVERNMENT; CARIBBEAN